TASK-BASED LANGUAGE TEACHING IN THE ESL CLASSROOM: A PEDAGOGICAL PERSPECTIVE - Xomidjonova Gavharoy Xayrullo qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Task-Based  Language  Teaching  (TBLT)  has  emerged  as  an influential approach in English as a Second Language (ESL) classrooms, emphasizing the use of meaningful tasks to promote communication and language acquisition. This article explores the pedagogical foundations of TBLT and its practical application in ESL contexts. It analyzes how task design, sequencing, and assessment contribute to learner  engagement  and  fluency  development.  The  study  also  discusses  challenges faced by educators, including task complexity, classroom management, and learner readiness.  Findings  suggest  that  TBLT  fosters  authentic  language  use  and  learner autonomy, but its effectiveness depends on strategic planning and teacher expertise.